Time perspective as a predictor of academic competence among black first-year students in the Humanities - Steyn, Rinet (University of the Free State, 2012)
𝑬𝒏𝒈𝒍𝒊𝒔𝒉 The aim of the study was to explore the constructs of academic competence and time perspective amongst a population of Black African first-year students from the Faculty of the Humanities at the University of the Free State. A mixed method design was implemented to investigate the research aims in a conclusive manner. The potential of time perspective to predict academic competence was investigated during the quantitative phase. Greater in-depth knowledge was gained by exploring the participants' understanding of the constructs in the qualitative phase. In the quantitative phase of the study, participants' time perspective was measured with the Zimbardo Time Perspective Inventory (ZTPI), which divides time perspective into five frames: past-positive, past-negative, present-hedonistic, present-fatalistic, and future. Academic competence was conceptualised as the average result of all the modules that the participants had completed during 2011. A multiple regression analysis was conducted in order to measure the amount of variance in academic competence that is accounted for by time perspective. The quantitative results did not indicate a significant predictive value of time perspective in relation to academic competence. However, the past-negative time frame showed a significant negative correlation with academic competence. During the qualitative phase of the study, focus group sessions and individual interviews were conducted with a select number of participants in order to explore their personal understanding of the relevant constructs. A thematic analysis identified the challenges that were unique to the population as forces that limit academic competence. It was also found that participants apply different time frames and utilise all as motivational forces for achieving academic competence. The way in which social relationships are related to time perspective was identified as an important role player in participants' engagement with their studies. ___________________________________________________________________

𝑨𝒇𝒓𝒊𝒌𝒂𝒂𝒏𝒔 Die doe! van die studie was om die veranderlikes van akademiese prestasie en tydperspektief onder 'n populasie van Swart Afrika eerstejaarstudenteaan die Fakulteit van die Geesteswetenskappe in die Universiteit van die Yrystaat te ondersoek. 'n Gemengde metode is as navorsingsontwerp gelmplementeer om die navorsingsvrae op 'n beslissendewyseaan te spreek. Die potensiaal van tydperspektief om akademiese prestasie te voorspel is tydens die kwantitatiewe fase ondersoek. Meer in-diepte kennis oor die deelnemers se begrip van die veranderlikes is tydens die kwalitatiewe fase verkry. Tydens die kwantitatiewe fase van die studie is die Zimbardo Time Perspective Inventory {ZTPI) gebruik om die deelnemers se tydperspektief te assesseer. Tydperspektiefwordin vyf raamwerke verdeel, naamlik: verlede-positief, verlede-negatief, hede-hedonisties, hede-fatalisties en toekoms. Akademiese prestasie is gekonseptualiseer as die gemiddelde resultaat van alle modules wat die deelnemers tydens 2011 geneem het.'n Meervoudige regressiewe analise is toegepas om die variansie van akademiese prestasie wat deur tydperspektief verklaar word, te verkry. Die kwantitatiewe resultate het geen beduidende voorspellende waarde tussen tydperspektief en akademiese prestasie opgelewer nie.Die verlede-negatiewe tydraamwerk het wel 'n beduidende negatiewe korrelasie met akademiese prestasie aangedui. Gedurende die kwalitatiewe fase van die studie is fokusgroepe en individuele onderhoude met 'n geselekteerde hoeveelheid deelnemers gevoer om hulpersoonlike begrip van die relevante veranderlikes te bekom. 'n Tematiese analise het gedui op die unieke uitdagings wat die spesifieke populasie ervaar, wat akademiese prestasie beperk. Daar is ook gevind dat deelnemers verskillende tydraamwerke toepas, en elkeen as motivering tot akademiese prestasie gebruik. Die manier waarop sosiale verhoudings met tydperspektief verband hou, is ook as 'n belangrike rolspeler in die deelnemers se toewyding tot hul studiesgeïdentifiseer. ___________________________________________________________________
Dissertation (M.Soc.Sc.(Psychology))--University of the Free State, 2012
Keywords: Academic achievement; Higher education; South Africa; Bloemfontein; College freshmen; Academic competence; Time perspective; First-year experience; Black African students; Motivation; Goals; Hope